Analisis Kinerja Mikro Turbin Gas Bahan Bakar LPG (Liquefied Petroleum Gas) - Qardhawi, Youssuf; Ghaffar, Nurshofi; Prasetyo, Eko; Hermawan, Rudi; Pane, Erlanda Augupta (Rekayasa, 2021)
The Micro Gas Turbine is a device that functions to convert chemical energy from fuel from the combustion process into mechanical energy, which is then converted back to a generator to become electricity. This study aims to obtain the results of performance testing as well as the results of the comparison analysis of the Gas Turbine Micro from the design and testing of the assembly tool. The fuel used in this Gas Micro Turbine is LPG (Liquefied Petroleum Gas). The advantages of LPG are it is easy to obtain, has a high octane value so that the power generated is greater, has a high vapor pressure so there is no need to use a pump to drain it. The result of this research is that the addition of a fire source can increase the turbine inlet temperature although it is not significant because the fire does not burn continuously due to the compressor rotation being too forceful. In the first and second actual tool tests, the temperatures were 317.48K and 323.75 K, different from the results of the analysis on the ANSYS software where the temperature was 766 K and 793 K.